Improving workplace mental health: a training needs analysis to inform beyondblue's online resource for leaders. (12th March 2014) - Shann, Clare; Martin, Angela; Chester, Andrea
<x xml:space="preserve">Abstract</x> The management of employees with mental health problems in the workplace is an emerging organisational challenge for leaders and HR managers. Training programs on this topic are increasingly being implemented in organisations. However, this training is rarely built into leadership programs, and relevant skills and attitudes can fail to be sustainably integrated into organisational cultures. The aim of this study was to investigate the training needs of leaders. A survey of 379 leaders and 364 HR and learning and development professionals was undertaken. The majority of leaders surveyed had experienced a situation requiring management of mental health in the workplace and recognised the importance of workplace strategies. However, very few had participated in mental health training. Discrepancies between rated levels of importance and confidence on a range of relevant skills and knowledge areas were identified. These findings highlight for HR professionals the priorities for the design of leader‐focused workplace mental health training. Such content prioritisations are critical to ensure engagement of time‐poor leaders is maximised.